Forest fragmentation and heterogeneity shape the occurrence of woodpecker species in Central Europe - Michał Bełcik; Bartłomiej Woźniak; Piotr Skórka (Scientific Reports)
Abstract The study investigates the impact of fragmentation metrics and other forest characteristics on the occurrence and richness of woodpecker species in 163 forest patches in Southern Poland. Generalised linear mixed models were used to estimate the influence of fragmentation metrics (patch size, nearest-neighbour distance, proximity index, patch shape) and forest stand features (age, proportion of coniferous tree species, proportion of dominant tree species) on woodpecker presence and woodpecker species richness. Eight woodpecker species were identified during surveys, and the study found that forest patch size positively correlated with the probability of occurrence for the great spotted woodpecker and black woodpecker but negatively with the occurrence of wryneck. The nearest-neighbour distance between two forest patches and the proximity index were negatively correlated with the occurrence of the lesser spotted woodpecker. The shape index negatively influenced the occurrence of the great spotted woodpecker but positively the occurrence of the wryneck. The European green woodpecker occurrence probability decreased with the proportion of coniferous tree species. Woodpecker species richness was positively associated with forest patch size and age, but negatively with the proportions of coniferous trees and dominant tree species. These findings indicate that forest fragmentation is a major driver of woodpecker species occurrence and richness, along with habitat quality characteristics.